1998
DOI: 10.1128/mcb.18.4.2184
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BCE-1, a Transcriptional Enhancer Regulated by Prolactin and Extracellular Matrix and Modulated by the State of Histone Acetylation

Abstract: We have previously described a 160-bp enhancer (BCE-1) in the bovine ␤-casein gene that is activated in the presence of prolactin and extracellular matrix (ECM). Here we report the characterization of the enhancer by deletion and site-directed mutagenesis, electrophoretic mobility shift analysis, and in vivo footprinting. Two essential regions were identified by analysis of mutant constructions: one binds C/EBP-␤ and the other binds MGF/STAT5 and an as-yet-unidentified binding protein. However, no qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 69 publications
(60 reference statements)
2
94
1
Order By: Relevance
“…Previous studies examining regulation of the MMTV promoter by HDAC inhibitors found that, depending on a variety of conditions, butyrate or TSA could activate or repress the MMTV promoter in organized chromatin (Bresnick et al, 1990;Bartsch et al, 1996;Lambert and Nordeen 1998;Myers et al, 1998;Wilson et al, 2002). Repression was observed in seven distinct cell lines with two exceptions.…”
Section: Effects Of Tsa On Mmtv Transcriptionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies examining regulation of the MMTV promoter by HDAC inhibitors found that, depending on a variety of conditions, butyrate or TSA could activate or repress the MMTV promoter in organized chromatin (Bresnick et al, 1990;Bartsch et al, 1996;Lambert and Nordeen 1998;Myers et al, 1998;Wilson et al, 2002). Repression was observed in seven distinct cell lines with two exceptions.…”
Section: Effects Of Tsa On Mmtv Transcriptionmentioning
confidence: 91%
“…This promoter, when assembled into organized chromatin, can be repressed by the HDAC inhibitors trichostatin A (TSA) or sodium butyrate at concentrations which cause the accumulation of acetylated histones (Bresnick et al, 1990;Bartsch et al, 1996;Lambert and Nordeen 1998;Myers et al, 1998;Wilson et al, 2002). We have investigated the mechanism by which TSA represses the MMTV promoter in organized chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized previously that the structural continuity that exists between the ECM, integrins, the cytoskeleton and the nuclear matrix may regulate the access of transcription factors to their target genes, perhaps through modulation of histones and chromatin structure [5,13]. Consistent with this notion, in mammary epithelial cells, where β1 integrin ligation, tyrosine kinase signalling and morphological changes induced by basement membrane are all required for transcriptional activation of the milk protein β-casein, access of transcription factors to the β-casein gene depends ultimately upon chromatin organization [95]. Therefore it is likely not only that cell shape permits the interaction of upstream effectors, such as Ras and Raf, with downstream mediators including ERKs, but that cell shape also influences the interaction of these downstream mediators with their growth-or differentiation-specific target genes at the level of nuclear structure ( Figure 3).…”
Section: Figure 2 Cell-shape-dependent Coupling Of the Ecm/integrin Amentioning
confidence: 97%
“…The extracellular matrix (ECM) induces a complex interaction between bound transcription factors, the basal transcriptional machinery, and a chromosomally integrated template responsive to the acetylation state of the histones at the β-casein enhancer and promoter regions (Myers et al 1998). There is evidence suggesting that the ECM maintains a high level of histone H4 acetylation upstream of the αs1-casein gene, especially at the level of a distal prolactin and ECM-sensitive enhancer region (Jolivet et al 2005).…”
Section: Adhesion Signaling In Mammary Epithelial Cell Differentiatiomentioning
confidence: 99%